Impact of meningococcal ACWY conjugate vaccines on pharyngeal carriage in adolescents: evidence for herd protection from the UK MenACWY programme. (December 2022) - Carr, Jeremy P.; MacLennan, Jenny M.; Plested, Emma; Bratcher, Holly B.; Harrison, Odile B.; Aley, Parvinder K.; Bray, James E.; Camara, Susana; Rodrigues, Charlene M.C.; Davis, Kimberly; Bartolf, Angela; Baxter, David; et al.
Abstract: Objective: Serogroup W and Y invasive meningococcal disease increased globally from 2000 onwards. Responding to a rapid increase in serogroup W clonal complex 11 (W:cc11) invasive meningococcal disease, the UK replaced an adolescent booster dose of meningococcal C conjugate vaccine with quadrivalent MenACWY conjugate vaccine in 2015. By 2018, the vaccine coverage in the eligible school cohorts aged 14 to 19 years was 84%. We assessed the impact of the MenACWY vaccination programme on meningococcal carriage. Methods: An observational study of culture-defined oropharyngeal meningococcal carriage prevalence before and after the start of the MenACWY vaccination programme in UK school students, aged 15 to 19 years, using two cross-sectional studies: 2014 to 2015 "UKMenCar4" and 2018 "Be on the TEAM" (ISRCTN75858406). Results: A total of 10 625 participants preimplementation and 13 438 postimplementation were included. Carriage of genogroups C, W, and Y (combined) decreased from 2.03 to 0.71% (OR 0.34 [95% CI 0.27–0.44], p < 0.001). Carriage of genogroup B meningococci did not change (1.26% vs 1.23% [95% CI 0.77–1.22], p = 0.80) and genogroup C remained rare (n = 7/10 625 vs 17/13 438, p = 0.135). The proportion of serogroup positive isolates (i.e . those expressing capsule) decreased for genogroup W by 53.8% (95% CI -5.0 – 79.8, p = 0.016) and for genogroup Y by 30.1% (95% CI 8.946·3, p = 0.0025). Discussion: The UK MenACWY vaccination programme reduced carriage acquisition of genogroup and serogroup Y and W meningococci and sustained low levels of genogroup C carriage. These data support the use of quadrivalent MenACWY conjugate vaccine for indirect (herd) protection. Graphical abstract: Image 1